Reduced folate carrier-1 80G > A gene polymorphism is not associated with methotrexate treatment response in South Indian Tamils with rheumatoid arthritis. Issue 4 (April 2016) - Muralidharan, Niveditha; Mariaselvam, Christina; CB, Mithun; Negi, Vir
Abstract Methotrexate (MTX) is the most commonly used disease-modifying drug to treat rheumatoid arthritis (RA). Although there are no reliable molecular markers to predict the treatment response and adverse effects to MTX therapy, the polymorphisms in genes coding for MTX metabolizing enzymes and transporters may play a crucial role. The reduced folate carrier-1 (RFC -1) is a bidirectional anion exchanger which transports MTX and folinic acid. It is reported to influence MTX treatment response and adverse effects in some ethnic populations but not in others. It is also associated with susceptibility to various diseases including systemic lupus erythematosus (SLE). The present study was aimed at investigating the role ofRFC -1 80G > A gene polymorphism in association with disease susceptibility, MTX treatment response and the MTX-induced adverse events in the South Indian Tamil patients with rheumatoid arthritis. TheRFC -1 80G > A gene polymorphism was investigated in 327 patients with RA and in 322 healthy controls by PCR-RFLP method. It was found that the heterozygousRFC -1 80 GA genotype was associated with protection against RA [p  = 0.02, odds ratio (OR) 0.69, 95 % confidence interval (CI) 0.50–0.95]. However, it was not found to be associated with MTX treatment response. TheRFC -1  G allele frequency was higher in patients with adverse effects, but the difference was not statistically significant (p  = 0.08, OR 1.44, 95 % CI 0.97–2.13).RFC -1 80G > A gene polymorphism confers protection for RA. However, it is not associated with MTX treatment response and MTX-induced adverse effects in South Indian Tamil patients with RA.